Bacteriological Effects of Dentifrices with and without Active Ingredients of Natural Origin - Ledder, Ruth G. (American Society for Microbiology, 2014)
Compounds of natural origin are increasingly used as adjuncts to oral hygiene. We have adopted four distinct approaches to assess the antibacterial activity of dentifrices containing natural active ingredients against oral bacteria in several test systems. Corsodyl Daily (CD), Kingfisher Mint (KM), and Parodontax fluoride (PF) were compared to a dentifrice containing fluoride (Colgate Cavity Protection [CCP]) and one containing triclosan (Colgate Total [CT]). The growth inhibitory and bactericidal potency of the formulations were determined for 10 isolated oral bacteria. Effects of single exposures of simulated supragingival plaques were then determined by epifluorescence and confocal microscopy, while the effects of repeated exposures were quantified by viable counting. Additionally, dense plaques, maintained in continuous culture, were repeatedly dosed, and the outcome was assessed by viable counting and eubacterial DNA profiling. The test dentifrices exhibited variable specificity and potency against oral bacteria in axenic culture. Of the herbal formulations, KM caused the largest viability reductions in simulated supragingival plaques, with CT causing the greatest reductions overall. Following single exposures, CD caused moderate reductions, while PF had no effect. After multiple dosing, all formulations significantly reduced numbers of total, facultative, and Gram-negative anaerobes, but only KM and CT caused greater reductions than the fluoride control. KM also reduced counts of streptococci (rank order of effectiveness: CT > KM > CCP > PF > CD). Marked changes in eubacterial DNA profiles were not detected for any herbal formulation in dense plaques, although KM markedly reduced viable counts of streptococci, in agreement with supragingival data. While both nonherbal comparators displayed antibacterial activity, the triclosan-containing formulation caused greater viability reductions than the herbal and nonherbal formulations.